A comparison of two different methods for time-motion analysis in team sports - Dogramaci, S. N.; Watsford, M. L. (International Journal of Performance Analysis in Sport, 2007)
Time-motion analysis has been extensively used to provide an insight into the movement patterns of athletes in team sports. However, few studies have indicated whether analysis involved breaks in play, or all the activities within the standard clock-time. Therefore, the purpose of this study was to differentiate whether differences existing between clock-time and match-time time-motion analysis had an affect on the results. Data was collected from the Australian National Futsal Team. Analysis was initially conducted against the actual playing clock-time of 40 min, then on a match-time of 70 min including all actions and breaks in play, excluding half-time and time-out intervals. When comparing match-time to clock-time data, there was a 16% greater total overall distance covered, a 6.9% increase in the time spent in low-intensity activities, and a change in activity every 4.00 s vs. 3.28 s, respectively. There was little change in the high-intensity activities from clock-time to match-time comparison. As clock-time data may misrepresent the movement patterns of the game, it is important to establish a standard method of analysis, namely based on match-time data. This may have implications on similar sports based on clock-time such as water polo, basketball, ice hockey and handball.